Aplicación de un programa de enriquecimiento ambiental y evaluación de la respuesta conductual del Tapir Amazónico (Tapirus terrestris) cautivo en el bioparque Orillas del Zamora. - Cuenca Ruíz, Katherine Natalie (2019)
This research was carried out in the Biopark "Orillas del Zamora" which is located in the city of Loja where an environmental enrichment program was applied to two Amazon Tapirs (Tapirus terrestris) (female and male) that are under captive conditions, in order to evaluate their behavioral response before and after this program. At the same time as determining whether or not visitors constitute a stressor to them. The independent studied variables were the visitors and the type of enrichment while the dependent variable was the behavioral response. All the evaluations were carried out at the same time in the morning from 10:30 am to 11:30 am and in the afternoon from 3:00 pm to 4:00 pm. In the same way, the observations were direct and indirect through a video camera, whereas the sampling was focal and its registration was continuous. Initially, a pre-observation stage was carried out to determine and define the most frequent behavioral units with which the ethogram was designed and developed. This allowed to evaluate the behavior in the pre and post enrichment stages, for the more the behavior with and without visitors. Was also evaluated six types of environmental enrichments were applied: two nutritional, two physical and two sensorial. The Chi square test (X2) was calculated, as well as the Kruskal Wallis test, and the Spearman rank correlation to detect if there were significant variations in the studied variables. As a result, ten behavioral units were identified, out of which food, exploration and rest alertly were those that were significantly different after enrichment, reducing total rest and the expression of repetitive movements. It is concluded that the applied environmental enrichment program had positive effects on the behavior of the Amazonian Tapirs (Tapirus terrestris) under study, which can be confirmed with the observation of behaviors characteristic of the species that have increased are more frequently observed such as feeding and exploration. In addition, apparently visitors are not a stressor for these tapirs due to their familiarity with them. Keywords: animal behavior, animal welfare, stereotyping, ethogram, visitors.